Short ejaculatory abstinence in normozoospermic men is associated with higher clinical pregnancy rates in sub-fertile couples undergoing intra-cytoplasmic sperm injection in assisted reproductive technology: A retrospective analysis of 1691 cycles - Sweta Gupta; Vikram J Singh; Ashish Fauzdar; Kamta Prasad; Ajay Srivastava; Kamlesh Sharma (Wolters Kluwer Medknow Publications, 2021)
Background: The current WHO abstinence recommendations are ideal only for clinical diagnosis, as in recent years a negative correlation of abstinence duration with good embryo development and clinical pregnancy rate has been seen. Aim: The aim of the study was to evaluate the impact of variation in abstinence period on fertilization, embryo development potential, pregnancy, and miscarriage rate in sub-fertile couples undergoing assisted reproductive technology (ART) treatment. Setting and Design: A prospective analysis was conducted at a tertiary (level 3) infertility care clinic. Materials and Methods: The study included analysis of 1691 cycles for the patient undergoing ART procedures between September 2017 and August 2019. The influence of ejaculatory abstinence (EA) was investigated based on variation in abstinence length with four groups: Group I - 1 day; Group II - 2-5 days; Group III - 6-7 days; and Group IV - EA length of ≥8 days. Statistical Analysis: Analysis of variance and Chi-square test were used to calculate P value. Results: In our primary outcome, we have seen a strong positive correlation of abstinence duration with semen volume, total sperm count, total motile count, and difference between each group was significant. Secondary outcomes showed a significantly higher implantation rate, biochemical pregnancy rate was observed in Group I (1 day) per embryo transfer as compared to longer abstinence groups. This resulted in significantly higher clinical pregnancy rates in Group I 30.0% vs. 25.4% in comparison to longer abstinence groups. Conclusions: Our study has shown duration of abstinence is negatively correlated with positive β-human chorionic gonadotropin rate, clinical pregnancy rate, and implantation rate. Lower miscarriage rate was also observed with shorter abstinence duration.